Urban History: Elaboration of Research Area - Бетлій, Олена (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
The article examines urban history as a separate research area within history studies. The author has analyzed how Ukrainian and foreign researchers have outlined its tasks, what discussions have been conducted on its content. Besides, the author has defined the most promising research areas within urban history approach. In addition, she has tried to elaborate the differences between urban history and other research strategies and take into consideration some challenges which any historian who is approaching history of towns and cities is facing.